Effect of the Operating Variables on the Extraction and Recovery of Aroma Compounds in an Osmotic Distillation Process Coupled to a Vacuum Membrane Distillation System - Romero-Figueroa, J; Torres-Mediano, A; Plaza, A (2012)
Sin Editorial Disponible